Fidel Ilizástigui Dupuy and his conception of education at work - Alfonso de León, José Alberto; Mondéjar Rodríguez, Juan Jesús; Blanco Aspiazu, Miguel Ángel (Atenas, 2016)
Fidel Ilizástigui Dupuy is regarded as a paradigm because of his contribution to medical education, mainly by his concept “education at work”. Through his life and labor he created this concept, based on his Marxist–Leninist philosophic conception, Marti’s ideas, his fidelity to the Revolution, his deep study and his experience in Cuba and other countries finally considering “education at work” as Cuban Medical Education rector principle. The studies of his pedagogic thoughts and of his contribution to educational organization forms will allow raising the quality of teaching and assistance.